Performance of parthenocarpic and non-parthenocarpic grafts of cucumber - POOJA P GOWDA; Rafeekher M.; SARADA S (Journal of Horticultural Sciences, 2022)
Effect of rootstock on yield and quality of cucumber scion was studied at Department of Vegetable Science, College of Agriculture, Vellayani, Thiruvananthapuram, Kerala during February-May, 2021. Parthenocarpic and non-parthenocarpic cucumber scions were grafted onto five different cultivated cucurbit species i.e. pumpkin, bottle gourd, oriental pickling melon, culinary melon and ash gourd. Significant variations were observed for all the traits under this study. The highest vine length (4.37 m) was observed in Heera scion grafted onto Lagenaria siceraria rootstock followed by Heera scion grafted onto Cucurbita moschata rootstock (4.13 m). The diameter of rootstock hypocotyl was higher in case of KPCH-1 grafted onto bottle gourd (1.48 mm) and Heera grafted onto bottle gourd (1.43 mm). KPCH-1 grafted on bottle gourd (29.33 days) and culinary melon (31 days) rootstocks showed early female flower initiation. The greater number of fruits was observed in graft combination of KPCH- 1 and bottle gourd (32) followed by parthenocarpic grafts with pumpkin (30.33) and ash gourd (30.33) rootstocks. A greater fruit weight was observed in graft combination of Heera and bottle gourd (7.51 kg) followed by Heera grafted onto pumpkin (7.38 kg). Results of this experiment suggest that these graft combinations can be employed in sustainable vegetable cultivation.